UJI METODE ANALISIS MINYAK TERDISPERSI DALAM AIR - Nuryatini, -; Wiloso, Edi Iswanto (Teknologi Indonesia, 2010)
Test on the method of analysis to determine oil dispersed in water has been carried out using an instrument, OCMA-350 Horiba based on infra red absorption. The oil samples used in this test were B-heavy oil, cutting oil, and diesel oil. The results of the experiment indicate that the calibration of the OCMA -350 Horiba needs to be done by using the standard oil according to the type of oil tested. The use of the method for all oil tested shows good results. The B-heavy oil in the water with a concentration 179 mg/L gave a recovery of 99.04%, with variant coeffi cient 1.48% and detection limit of 0.54 mg/L. Similarly, the cutting oil with concentration 178 mg/L gave a recovery value of 99.51%, with variant coeffi cient of 2.49%. Finally, the analysis of diesel fuel in the water at concentration of 84 mg/L gave a recovery value of 100.32% with variant coeffi cient 3.71%